Groundwater Depletion: A Significant Unreported Source of Atmospheric Carbon Dioxide. Issue 11 (16th November 2017) - Wood, Warren W.; Hyndman, David W.
Abstract : Quantifying the annual flux of CO2 (carbon dioxide) and equivalent emissions to the atmosphere is critical for both policy decisions and modeling of future climate change. Given the importance of greenhouse gas emissions to climate change and a recognized mismatch between sources and sinks (e.g., Liu & Dreybrodt, 2015), it is important to quantify these parameters. A significant and previously unrecognized CO2 contribution arises from groundwater depletion (net removal from storage). The average annual 1.7 MMT (million metric tons) CO2 released in the United States from this source is greater than approximately one third of the 23 major sources reported by the US EPA (United States Environmental Protection Agency) to the IPCC (Intergovernmental Panel on Climate Change; US EPA, 2016 ). Key Points: Significant and previously unidentified CO2 source to the atmosphere Plain Language Summary: We suggest that groundwater depletion adds significant and measurable CO2 to the atmosphere and should be considered as a source in future CO2 budgets as groundwater depletion at the same or greater rate is likely to continue